DAMAGE DETECTION IN STRUCTURES: FROM MODE SHAPE TO FREQUENCY RESPONSE FUNCTION METHODS - MAIA, N.M.M.; SILVA, J.M.M.; ALMAS, E.A.M.; SAMPAIO, R.P.C. (Mechanical systems and signal processing, 2003)
The present paper addresses the subject of damage detection in structures. A series of numerical simulations on a simple beam are made in order to compare various damage detection methods based on mode shape changes. A generalisation of these methods to the whole frequency ranges of measurement is proposed, i.e. methods based on mode shape changes become based on operational mode shapes. The objective of such a study is to ascertain the possibility of using various damage detection methods without the need for modal identification. In recent years, the authors have developed some simple methods and tools based upon the use of frequency response functions (FRFs), which seem promising and have given good results in some practical applications. Here, some of that work is applied to the new proposed FRF-based methods which are compared and discussed. Numerical simulated examples will be used, as well as an experimental test case, where damage is inflicted in a free–free beam.